Peningkatan Kapasitas Petani Melalui Pengolahan Sawi Hijau di Desa Pejarakan Karya Kecamatan Ampenan - Widiyanti, Ni Made Nike Zeamita Widiyanti; Yusuf, M.; Husni, Syarif; Nursan, Muhammad; Hidayanti, Anna Apriana (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Green mustard is a vegetable that is generally used by the community as food to be processed into vegetables. Besides having benefits for the health of the body, green mustard also has economic value that can be processed into various kinds of processed products, one of which is green mustard noodles. Fresh green mustard has a fairly short shelf life, so farmers must sell it immediately after harvest. If the vegetables are not sold in the market, the mustard greens will wither and spoil. Based on this problem, it is necessary to hold training on green mustard processing to extend the shelf life of mustard and increase farmers' income through added value of green mustard processing.   The method of implementing the service was carried out using the lesson study method. This method consists of 2 stages, namely: the planning stage and the implementation stage. This green mustard processing training has increased the knowledge and skills of the participants in processing green mustard into noodles. This activity processes green mustard into noodles which can be used as another business opportunity for participants. In general, this service activity was rated very well by the participants.